Johan Cruyff and his contribution to success and stadium attendance at Feyenoord - Jan C. van Ours (Tinbergen Institute, 2021)
In his last season as professional football player, Johan Cruyff played at Feyenoord. This paper shows that Cruyff improved the performance of his team and provides evidence of his presence attracting more stadium attendants to the home ground. From this it is concluded that Cruyff made a superstar contribution to his club Feyenoord.
Keywords: Z21; D12; C23; 330; professional football; superstar; Johan Cruyff; Feyenoord